Crecimiento de la inversión extranjera de los Estados Unidos de América en Colombia (2010-2020) (2021)
Foreign Direct Investment (FDI) is recognized by multiple stakeholders of the worldwide economy as an indicator of development, growth and proliferation of the nation. An appropriate regulation for FDI can bring employment, diversification of the industries, and a real reason why to innovate in the local markets where small business can realize the need to be competitive. However, FDI has its negative side that have to be strictly and extremely regulated by macroeconomic policies.